A local search heuristic to solve the planning problem of 3G UMTS all-IP release 4 networks with realistic traffic. (1st January 2014) - Pasandideh, Mohammad Reza; St-Hilaire, Marc
The purpose of this paper is to develop an efficient heuristic in order to solve the planning problem of 3rd Generation (3G) Universal Mobile Telecommunication System (UMTS) all-IP Release 4 networks. Since the problem is NP-hard, an approximate algorithm based on the local search principle is proposed. Targeting a realistic planning tool, a realistic traffic profile was taken from real live networks. To evaluate the efficiency of the proposed heuristic, a comparative study in which the results are compared with respect to a reference model is conducted. Numerical analysis demonstrates that the local search algorithm produces solutions that are, on average, within 5.03% of the optimal solution, and in the best and worst cases at 0.87% and 9.29% of the optimal solution respectively.